An investigation into the relationship between design approaches, student engagement and agency in a blended learning computer science course - Van Der Merwe, Brendan Kenneth (School of Education, 2025)
Disengagement among learners in tertiary Computer Science (CS) courses, particularly those focusing on algorithmic design, poses challenges to the achievement of learning outcomes. This study explores the relationship between learning design approaches, meaningful learner engagement, and agency in the context of a blended learning CS theory course at a tertiary level. As technology provides new opportunities for pedagogical practices, gaining insight into how agency and learning design approaches affect learners' experiences has the potential to enhance education in South Africa (SA) and globally. This study utilises a mixed-methods research design, integrating both quantitative and qualitative data collection techniques. A comprehensive questionnaire was administered to learners to determine their perceptions of engagement and agency, assisting in identifying nuances that informed the design and development of learning activities within the course. After the implementation of the learning activities, a second questionnaire was administered to evaluate their overall effectiveness. Additionally, in-depth interviews (see Appendix C) were conducted with a subset of participants to capture valuable qualitative insights. The Social Realism (SR) theory of Margaret Archer (1995, 2003, 2006) was used to understand learner agency and their personal concerns that inform their courses of action. Archer's (2007b) analytical dualism approach, which separates culture, structure, and agency, was followed to examine the interrelation between these three dimensions. The findings of this study reveal an enabling relationship between the incorporation of design approaches and heightened learner engagement. Learners reported a greater sense of motivation, enthusiasm, and connection to the subject matter when certain design methods were integrated into learning activities. Furthermore, the qualitative data highlighted agency among learners, as they assumed more active roles in their learning, ultimately leading to a deeper understanding of algorithm design in CS. A conceptual framework, the Meaningful Engagement (ME) framework, is presented in this study, providing valuable insights for educators, curriculum developers, and instructional designers seeking to enhance meaningful learner engagement and agency in blended learning environments. Furthermore, this study contributes to the ongoing discourse on the integration of engaging pedagogical practices in higher education, shedding light on the benefits of design approaches in enriching the learner experience and promoting agency that empowers the learner.